2020
DOI: 10.7717/peerj.8650
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study: clinicopathological features and prognosis of idiopathic membranous nephropathy with seronegative anti-phospholipase A2 receptor antibody

Abstract: Background To discuss the clinicopathological features and prognosis of patients with idiopathic membranous nephropathy (IMN) who are serum-negative for the anti-PLA2R antibody. Method Overall, 229 IMN patients were retrospectively collected in this study and classified into anti-PLA2R antibody-negative (PLA2R−, 59 cases) and antibody-positive (PLA2R+, 170 cases) groups. The clinical and pathological features of the PLA2R− group were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Serum albumin and urinary protein are generally used to quantitatively evaluate the severity of nephrotic syndrome in MN, which are important indicators for assessing disease activity ( Kanigicherla et al, 2013 ; Lin et al, 2015 ; Gopalakrishnan et al, 2016 ; Li et al, 2016 ). Consistent with data from aforementioned studies ( Li et al, 2016 ; Song et al, 2018 ; Provatopoulou et al, 2019 ; Katsumata et al, 2020 ; Li et al, 2021 ), we found a significant association of PLA2Rab with urinary protein and serum albumin indicating the correlation between antibody levels and disease activity ( Mahmud et al, 2019 ; Gong et al, 2020 ; Guo et al, 2020 ). However, Jullien et al (2017 ) claimed that the initial PLA2Rab level did not relate to the degree of proteinuria.…”
Section: Discussionsupporting
confidence: 91%
“…Serum albumin and urinary protein are generally used to quantitatively evaluate the severity of nephrotic syndrome in MN, which are important indicators for assessing disease activity ( Kanigicherla et al, 2013 ; Lin et al, 2015 ; Gopalakrishnan et al, 2016 ; Li et al, 2016 ). Consistent with data from aforementioned studies ( Li et al, 2016 ; Song et al, 2018 ; Provatopoulou et al, 2019 ; Katsumata et al, 2020 ; Li et al, 2021 ), we found a significant association of PLA2Rab with urinary protein and serum albumin indicating the correlation between antibody levels and disease activity ( Mahmud et al, 2019 ; Gong et al, 2020 ; Guo et al, 2020 ). However, Jullien et al (2017 ) claimed that the initial PLA2Rab level did not relate to the degree of proteinuria.…”
Section: Discussionsupporting
confidence: 91%
“…Membranous nephropathy (MN), an autoimmune disease, is one of the frequent causes of end-stage renal disease in adults. A recent retrospective study has suggested that the incidence of IMN is increasing, especially in the younger ones [ 33 ]. Its therapeutic regimen also is unsatisfactory and controversial due to the heterogeneity of the disease, although approximately a third of patients will achieve spontaneous remission [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the level of antibody is closely related to disease activity. Our study of patients negatives for the anti-PLA2R antibody demonstrated that combined kidney tissue PLA2R and IgG4 staining can effectively improve the accuracy of disease diagnosis 5 .…”
Section: Introductionmentioning
confidence: 80%